ANALISIS PENERAPAN AKUNTANSI PERTANGGUNGJAWBAN SEBAGAI PENILAIAN KINERJA MANAJERIAL PADA CV. BERKAT TAGU SEJAHTERA - Silalahi, Evelin Roma Riauli; Lumban Gaol, Romasi; Sinuhaji, Oktavia Veronika Br (UNIKA Santo Thomas, 2024)
This research aims to determine the application of accountability accounting to managerial performance appraisal on CV. Berkat Tagu Sejahtera. Meanwhile, data collection is carried out by library research and field research techniques. The population in this research is financial statements and information on the application of accountability accounting. The samples in this research are the company's 2020 financial statements and secondary data such as organizational structure, budget, cost classification, accounting system and accountability report on CV. Berkat Tagu Sejahtera. The method in this research uses qualitative descriptive methods. The results of this study show that the application of accountability accounting on CV. Berkat Tagu sejahtera most of it has been applied by CV. Berkat Tagu Sejahtera, there are some that are not in accordance with accountability accounting theory, including: 1). In the organizational structure of CV. Berkat Tagu Sejahtera, the placement of every responsibility center in every section of the company has not placed it well enough. 2). In the classification of CV. Berkat Tagu Sejahtera costs, it has not separated between controlled and uncontrolled costs in the accountability report, so that the costs incurred have not been efficient. 3). In the classification of account code CV. Berkat Tagu Sejahtera, it has not linked it to any accountability center in the company. 4). On the CV Berkat Tagu Sejahtra accountability report on the realization of revenues and costs did not reach the targets that had been set. And in the performance appraisal of CV. Berkat Tagu Sejahtera, it has not conducted an evaluation and investigation in the managerial performance appraisal stage so that the application of accounting is responsible for the managerial performance appraisal on CV. Berkat Tagu Sejahtera, it has not run well because it has not been maximized in implementing accountability accounting according to existing accountability accounting theory.